(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The effect of malaria infection on hepatic and renal functions in pregnancywas investigated. Three malarious and non-malarious pregnant women of age ranges 15 to 40 years with a mean (SD) of 23.5 (6.6) years and a median (IQR) of 20.5 (18.3 to 27) years were enrolled. Liver enzymes (AST, ALT and ALP) and Kidney (UCE) functions were determined using Randox standard assay kits. The levels of alkaline phosphatase (ALP) and albumin were significant as malaria infected pregnant women had significantly lowered levels of ALP and albumin compared to controls (21.3 vs 26.1 IU/L, P = 0.03 and 4.8 vs 6.0 g/dl P = 0.02). There was no significant difference between malaria infected pregnant women and their non-malarious counterparts (P > 0.05) in their renal functions. There was no significant difference in mean concentrations of urea, creatinine, sodium, potassium and chloride regardless of the severity of malaria. Usually in pregnancy markers of liver function decrease due to expansion of extracellular fluid except alkaline phosphatase which is elevated due to its placental origin. Results of this study showed decreased level of ALP which could possibly be an indication that the parasite has not reached its hepatic stage. The severity of gestational malaria depends on the initial immunity of the pregnant woman. The impact of malaria on pregnancy and conversely, the impact of pregnancy on malaria, are two factors which must be put into consideration during gestational malaria